Cervical Lymph Node Metastasis in Chromophobe Renal Cell Carcinoma: A Case Report and Review of the Literature - Noureddine Bouadel; Fahd El Ayoubi; A. Anass Bennani-Baiti; Mohamed Anas Benbouzid; Leila Essakalli; Mohammed Kzadri; Ali El Ayoubi (Case Reports in Otolaryngology)
The metastasis of chromophobe renal cell carcinoma to head and neck region, described herein, has never been reported before to our knowledge. A 56-year-old woman with a history of nephrectomy, that revealed chromophobe renal cell carcinoma six years before, presented left cervical mass. Imaging showed with left cervical lymphadenopathies and thyroid nodule. Surgery with histopathological examination confirmed that it was a left central and lateral jugular lymph node metastasis of chromophobe renal cell carcinoma treated postoperatively by antiangiogenic therapy. The patient was successfully treated by surgery and antiangiogenic drugs with stabilization and no recurrence of the metastatic disease. The case and the literature reported here support that chromophobe renal cell carcinoma can metastasize to the head and neck region and should preferentially be treated with surgery and antiangiogenic therapy because of the associated morbidity and quality-of-life issues.